The Effect of Chemotherapeutic Agents on Survival in Metastatic Non-Small-Cell Lung Cancer with KRAS Mutation - Duygulu, Mustafa Emre; Yildirim, Atila; Ayas, Eyyup; Alyildiz, Nese; Mungan, Sevdegul Aydin; Fidan, Evren (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction KRAS mutation is observed in up to 30% of non-small-cell lung cancer (NSCLC) cases and is corelated with a poor prognosis. In the cases with KRAS p.G12C mutation and first-line chemotherapy (± immunotherapy) resistance, a targeted drug option is available.Objectives Our study aimed to examine the correlation between first-line chemotherapy agents and treatment response in patients with KRAS-mutated metastatic NSCLC.Materials and Methods Retrospective database searches were performed on cases diagnosed with metastatic NSCLC at our center between January 2019 and December 2021 that were found to be KRAS mutation positive using the next-generation sequencing (NGS) approach. The cases were classified into five subgroups based on the chemotherapy regimens (platinum + gemcitabine, platinum + taxane, platinum + pemetrexed, platinum + vinorelbine, and others). The clinical and demographic data of 41 cases were analyzed retrospectively, and survival analyses were performed using the Kaplan–Meier method.Results Thirty-seven of 41 patients (90.2%) were males, and 27 (65.9%) had adenocarcinoma histology. The most prevalent mutation was KRAS G12C, with 12 cases (29.2%), followed by KRAS G12V, with 9 cases (21.9%). Other mutations were as follows: KRAS G12D 4 (9%), KRAS G13C 3 (7.3%), KRAS G12A 2 (4.8%), KRAS G12R 2 (4.8%), KRAS Q61H 2 (4.8%), KRAS Q61L 2 (4.8%), KRAS V14I 2 (4.8%), KRAS A146T 1 (2.4%), KRAS G13G 1 (2.4%), and KRAS G1C 1 (2.4%). The median progression-free survival (mPFS) for all groups was 4.6 months (95% confidence interval [CI]: 2.7-6.5), and there were no statistically significant differences between the groups (p = 0.121). The median overall survival (mOS) for all groups was 9.3 months (95% CI: 3.8–14.5), and there were no statistically significant differences between the groups (p = 0.805).Conclusions OS and PFS analyses showed no differences between platinum + taxane, platin + pemetrexed, platinum + gemcitabine, and platin + vinorelbine used in first-line treatments for KRAS mutant NSCLC cases. We believe that patient-specific characteristics may be a determining factor in selecting chemotherapy for this patient population.
Keywords: metastatic NSCLC; KRAS; chemotherapy; OS; PFS; platinum